Short-Term Lightning Response to Ground Level Enhancements - Wu, Qiong; Li, Hui; Wang, Chi (Frontiers in Physics, 2020)
Cosmic rays (CRs) are considered the primary energetic particle source of atmospheric ionization on Earth. Under the modulation of severe solar eruption events, CR variations are further speculated to impact the Earth’s lightning activities. Previous researches show that CR intensity and lightning incidence are positively correlated on the time scale of several days to decades. However, to our knowledge, the global lightning response to short-term CR variation has not been studied in the literature. Ground level enhancements (GLEs) provide the opportunity to study such a possible link. As a small fraction of solar energetic particle events that could reach the energy level of several GeVs, GLEs can thus generate atmospheric cascades that could be recorded by ground-based neutron monitors. Furthermore, as GLEs generally take place within several ten minutes to an hour, the lightning variations caused by potential meteorological factors could be maximally diminished in such a short time. During the operational period of the World Wide Lightning Location Network (Aug 2004 to now), three typical GLEs with the intensity greater than 15% are analyzed from the International GLE Database, namely #69 (Jan 20, 2005), #70 (Dec 13, 2006), and #71 (May 17, 2012). For each GLE event, the global lightning incidence presents a positive response to GLE, i.e., a significant enhancement within 20 minutes right after the GLE onset. Meanwhile, the relative amplitude of lightning response seems to be in direct proportion to GLE intensity, i.e., the more intensive the GLE is, the more obvious the increase in the lightning incidence is, which is further verified to be statistically significant by Monte Carlo test. By comparing lightning responses in different latitudinal zones, we find that more intensive lightning responses to GLEs seem to be at higher latitudes.